Teachers’ Judgments of Students’ School-Wellbeing, Social Inclusion, and Academic Self-Concept: A Multi-Trait-Multimethod Analysis Using the Perception of Inclusion Questionnaire - Schwab, Susanne; Alnahdi, Ghaleb Hamad (Frontiers in Psychology, 2020)
A Students’ school-wellbeing, social inclusion, and academic self-concept are considered important outcome variables of schools. In the present study, these three variables were examined from teachers’ and students’ perspective (grades 5–9). The Perception of Inclusion Questionnaire (PIQ) was administered to students (N = 699) and two main subject teachers (N=151 for each), and factor structure, reliability, and interrater overlap evaluated. The results for psychometric properties show that teachers’ version of the PIQ is suitable for secondary graders. Reliability was high (all α ≥ .83). The confirmatory factor analyses demonstrated good model fit for the three-dimensional factorial structure. The intraclass correlation for the two teachers’ ratings was high (all r ≥ .84). By excluding one teacher’s rating from the model, the multitrait-multimethod analysis provided indicators for the PIQ’s construct validity (convergent and discriminant validity) of the traits and discriminant validity of the methods.